P180 Vulval pathology in HIV positive women attending a tertiary vulval dermatology clinic over a 5-year period. (23rd May 2012) - Dosekun, O; Farrugia, P; Lewis, F; Sethi, G
Abstract : Background: Studies have suggested that HIV infected women are at increased risk of developing invasive vulval carcinoma and recurrent herpes simplex type 2 (HSV-2) reactivation. Objective: To describe the spectrum of HIV associated vulval disease in women attending a tertiary dermatology referral centre in a busy urban setting. Methods: A retrospective case note review of all HIV positive women seen in the vulval dermatology clinic from January 2007 to January 2012. Results: 11 women were identified (see abstract P180 table 1 ). 9 (81%) were black Africans. The mean age at vulval disease diagnosis was 37 years. Most (81%) were already known to be HIV infected and on combined antiretroviral therapy (cART). There were six cases of undifferentiated vulval intra-epithelial neoplasia (uVIN) (43%) with two cases being diagnosed prior to an HIV diagnosis. The three cases of HSV-2 occurred in women with near-complete immune restoration on cART. Six women remain under regular dermatology follow-up, a median of 20 months since diagnosis. Conclusion: There were no cases of invasive vulval carcinoma. HSV-2 may cause atypical disease even in the context of near-complete immune reconstitution on cART. Most women with vulval disease were already under HIV care, on cART and had a CD4 cell count above 200 cells/μl.